Improvement of California Bearing Ratio (CBR) Value of Clay Soil in Limau Manis Area, Padang by Using Lime and Rice Husk Ash - Candra, Prasetia Dego; Andriani, Andriani; Hakam, Abdul; Apdeni, Risma (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
Clay soil is known for its low bearing capacity, causing cracking or even collapse in construction. Soil improvement is needed before embanking into building on this type of soil. Methods to increase the bearing capacity of clay soil include compacting the soil or mixing it with additive materials that can improve soil properties. This study aimed to analyze the CBR value of clay soil in the Limau Manis hilly area, Padang City, with the addition of 5% lime and 2%, 4%, 6%, and 8% rice husk ash (RHA). The type of the soil is Organic Silt and Silty Clay (OL). This study conducted physical and mechanical properties of soil testing, i.e. sieve analysis, specific gravity, plastic limit, liquid limit, and CBR value. The results showed that adding 5% lime increased the CBR values of 0-day and 7-day cured soil, both in soaked and unsoaked conditions. The CBR value of the soaked and unsoaked 0-day cured soil sample increased by 189% and 168% respectively, while the CBR value of the soaked and unsoaked 7-day cured soil sample increased by 259% and 215% respectively. However, the addition of rice husk ash decreased the CBR value.